Pengaruh Label Halal Terhadap Keputusan Pembelian Produk Minyak Angin Aromaterapi Syifa Care Pada CV. Afsal Makmur - Andi Rifqah Purnama Alam; Andi Tendean (Jurnal Online Manajemen ELPEI, 2022)
This study aims to determine the effect of the halal label on consumer purchasing decisions for Syifa care aromatherapy wind oil products at CV. Afsal Makmur. The data used in this study are qualitative and quantitative. The data sources used in this research are primary and secondary data. The method used is descriptive answers to the questionnaire results with a Likert scale and statistical analysis in the form of simple regression analysis, correlation coefficient, coefficient of determination, and t test. the results of a simple regression analysis obtained the equation that is y = 8.137 + 0.49x, which means that there is a positive and significant influence between halal labels on consumer purchasing decisions for Syifa Care aromatherapy wind oil products at CV. Afsal Makmur. The results showed that the analysis of the correlation coefficient rxy 0.549 and r2 xy 0.3014 or 30.14% and obtained tcount of 5.06 is greater than ttable 1.6706 (5.06> 1.6706) with a significant level of 5% ( one side).